ANALISIS FAKTOR RISIKO KEMATIAN IBU (Studi Kasus di Kabupaten Banyumas) - Sri Rejeki, Dwi Sarwani; Nurlaela, Sri (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2013)
ABSTRACT Maternal Mortality Rate (MMR) is an indicator used to measure health developmen index, people?s prosperity or quality of life. Morbidity and mortality in women?s pregnancy and gavebirth was serious problem in developing country include Indonesia. MMR in Banyumas district was still high, in 2008 was 98,03 per 100.000 live births.The objective of this study was to indentify risk factors which influence with MMR.The type of this research was observational research with case-control design approach. There were 51 cases and 51 control sampling. As case group were maternal death in Banyumas district and control group was all mother live in pregnancy, gavebirth and postpartum and neigbour with case group. There are some significant risk factors that prove related with maternal death based on bivariat analysis: obstetrics complication, preexisting of disease, preexisting givebirth, mother ages, parity, interval time between childbirth, antenatal care, birth helper, mother?s education, mother?s work and family income. The result of multivariate analysis was complication obstetrics (OR= 31,9; 95% CI= 4,4 ? 188,9; p= 0,000), preexiting of disease (OR= 25,4; 95% CI=3,2 ? 176,1; p=0,001) and preexiting givebirth (OR=13,1; 95% CI=3,8 ? 147,2  p=0,001). Mother who are in pregnancy should do antenal care if they get obstetric complication and the disease can be detected as soon as posible, therefore it can be overcomed by medical threatment and counseling if theirs complain. Key word : risk factors, maternal death  Kesmasindo, Volume 6, ( 1 ) Januari 2013, Hal. 1-11